Magnetic properties of Fe-doped NiO nanoparticles - Alex Soares de Brito; Marlon Ivan Valerio-Cuadros; Lilian Felipe Silva Tupan; Aline Alves Oliveira; Reginaldo Barco; Flávio Francisco Ivashita; Edson Caetano Passamani; José Humberto de Araújo; Marco Antonio Morales Torres; Andrea Paesano, Jr. (Heliyon, 2023)
Undoped and Fe-doped NiO nanoparticles were successfully synthesized using a lyophilization method and systematically characterized through magnetization techniques over a wide temperature range, with varying intensity and frequency of the applied magnetic fields. The Ni1-xFexO nanoparticles can be described by a core-shell model, which reveals that Fe doping enhances exchange interactions in correlation with nanoparticle size reduction. The nanoparticles exhibit a superparamagnetic blocking transition, primarily attributed to their cores, at temperatures ranging from above room temperature to low temperatures, depending on the Fe-doping level and sample synthesis temperature. The nanoparticle shells also exhibit a transition at low temperatures, in this case to a cluster-glass-like state, caused by the dipolar magnetic interactions between the net magnetic moments of the clusters. Their freezing temperature shifts to higher temperatures as the Fe-doping level increases. The existence of an exchange bias interaction was observed, thus validating the core-shell model proposed.